Cell motility and ECM proteolysis regulate tumor growth and tumor relapse by altering the fraction of cancer stem cells and their spatial scattering. (28th April 2016) - Kumar, Sandeep; Kulkarni, Rahul; Sen, Shamik
Abstract: Tumors consist of multiple cell sub-populations including cancer stem cells (CSCs), transiently amplifying cells and terminally differentiated cells (TDCs), with the CSC fraction dictating the aggressiveness of the tumor and drug sensitivity. In epithelial cancers, tumor growth is influenced greatly by properties of the extracellular matrix (ECM), with cancer progression associated with an increase in ECM density. However, the extent to which increased ECM confinement induced by an increase in ECM density influences tumor growth and post treatment relapse dynamics remains incompletely understood. In this study, we use a cellular automata-based discrete modeling approach to study the collective influence of ECM density, cell motility and ECM proteolysis on tumor growth, tumor heterogeneity, and tumor relapse after drug treatment. We show that while increased confinement suppresses tumor growth and the spatial scattering of CSCs, this effect can be reversed when cells become more motile and proteolytically active. Our results further suggest that, in addition to the absolute number of CSCs, their spatial positioning also plays an important role in driving tumor growth. In a nutshell, our study suggests that, in confined environments, cell motility and ECM proteolysis are two key factors that regulate tumor growth and tumor relapse dynamics by altering the number and spatial distribution of CSCs.